061. A Rare Finding; Severe Intra Abdominal Infection and Colonic Necrosis in Geriatric Crohn’s Disease Patient - Tanaya, I Putu Denny; Irmayanto, Tomi; Abdillah, Abdillah; Zuhan, Arif; Ratna K.D, Baiq; Eka S, Herlina (JBN (Jurnal Bedah Nasional), 2024)
Background : Crohn's disease (CD) is an immune-mediated inflammatory bowel disease (IBD) marked by segments of transmural inflammation in the gastrointestinal tract. Only 10% to 15% of IBD cases occur in those over 65. In a retrospective study of 281 surgeries, 43 were in colitis patients and 242 in Crohn's patients. The mortality rate was 5.7%, with 9 deaths due to sepsis, mainly linked to emergency procedures and corticosteroid use. CD symptoms include fatigue, prolonged diarrhea, weight loss, and fever, with or without bleeding. Case : A 69-year-old female with a 15-day history of abdominal pain. Patient referred to our hospital after laparotomy and ileostomy 15-days ago. Patient condition worsened, sepsis condition. Upon arrival, the patient exhibited mild hypotension, abdominal distension with midline incision, intra abdominal drain, and an active ileostomy on the right lumbal region. Laboratory tests shows anemia, electrolyte imbalances, and hypoglycemia. A CT scan abdomen revealed pneumoperitoneum and intestinal inflammation. During relaparotomy operation, ileal perforation was found near the stoma, with full-thickness necrosis of the ascending colon extending into part of the transverse colon, and colitis with mucosal necrosis from part of the transverse colon to the rectum. So, we performed a total colectomy, and ileostomy relocation. Pathology confirmed Crohn's disease with granulomatous inflammation. The patient received intravenous fluids and antibiotics. She was subsequently admitted to the intensive care unit for further management. Conclusion: Crohn's disease with severe intra abdominal infected ec perforated colon in patients over 65 is a rare case. Timely diagnosis through detailed anamnesis and examination is crucial. Surgical options should be taken if there are signs of peritonitis.